Assessing the Impact of Human Development Index Components on Economic Growth: A Case Study of the Special Region of Yogyakarta - Budiyanto, Fajar Arif (University Merdeka Malang, 2024)
The study examines the influence of Human Development Index (HDI) components—education, health, and per capita expenditure—on the economic growth of the Special Region of Yogyakarta, Indonesia, from 2013 to 2022. Using panel data regression with the Common Effect Model, the research identifies the varying impacts of these components. Results indicate that education positively and significantly contributes to economic growth, while health and per capita expenditure exhibit a negative yet significant relationship. These findings highlight the importance of strategic policies to enhance human capital, reduce regional disparities, and optimize socio-economic outcomes. The study underscores the need for targeted public investments in education and healthcare infrastructure while addressing the unique economic challenges of areas with aging populations and low per capita expenditures. This research contributes to the growing body of literature on regional economic development and offers actionable insights for policymakers to foster sustainable economic growth.